2016
DOI: 10.1177/0890117116673820
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Lung Cancer Risk Prediction Models to Promote Smoking Cessation: Two Randomized Controlled Trials

Abstract: The current study suggests that lung cancer risk projections may help maintain abstinence among individuals who have quit smoking, but the results did not provide evidence to suggest that lung cancer risk projections motivate current smokers to quit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The majority ( n = 15) focused on provision of breast cancer risk derived from the Gail model [22], four provided risk information about colorectal cancer, one lung cancer, one cervical cancer, one colorectal and lung cancer, and one colorectal, breast and ovarian cancer. All but two studies [23,24] were conducted in the USA. Twelve were assessed as high or medium/high quality, seven as medium quality and four as medium/low based on the CASP guidelines (Appendix File A.2) [[25], [26], [27], [28], [29], [30]].…”
Section: Resultsmentioning
confidence: 99%
“…The majority ( n = 15) focused on provision of breast cancer risk derived from the Gail model [22], four provided risk information about colorectal cancer, one lung cancer, one cervical cancer, one colorectal and lung cancer, and one colorectal, breast and ovarian cancer. All but two studies [23,24] were conducted in the USA. Twelve were assessed as high or medium/high quality, seven as medium quality and four as medium/low based on the CASP guidelines (Appendix File A.2) [[25], [26], [27], [28], [29], [30]].…”
Section: Resultsmentioning
confidence: 99%
“…One high-quality RCT 23 reported the impact of risk information on smoking status. Receiving a personalised risk estimate in addition to a generic leaflet did not predict self-reported smoking status at 6 months in current smokers (P=0.66) but was associated with an increased odds of remaining a former smoker in those who had recently quit (OR 1.91 (95% CI 1.03 to 3.55)).…”
Section: Resultsmentioning
confidence: 99%
“…In a smoking cessation study, no relationship was found between a person being told their lung cancer risk and their 6month perception of personal cancer risk. 32 An individual's intrinsic understanding of their risk may trump calculated values. These findings support our hypothesis that concern for personal risk of lung cancer is likely to be a significant motivator for joining an LCS trial.…”
Section: Discussionmentioning
confidence: 99%